SISTEM PENCARIAN PRODUK HALAL BERBASIS ANDROID PADA PUSAT KAJIAN PRODUK HALAL (PKPH) UNMA BANTEN MENGGUNAKAN METODE WATERFALL - Eka Ridwan Ruswandi; Agung Sugiarto; Zaenal Hakim (Universitas Mathla’ul Anwar Banten, 2021)
The Center for Halal Product Studies (PKPH) UNMA Banten is a center for the study of halal products located at Mathla'ul Anwar University, Banten, chaired by Hadi Susilo, S.Si., M.Si. (Faculty of Science and Pharmacy) and has been established since April 2017. Many halal and non-halal products are sold in the market, but there are only a few reliable sources that provide information about certified halal products, and nowadays information must be obtained quickly anywhere and anytime. With the creation of this halal product search system, it is hoped that it can overcome these problems because this system is built and used for android phones that can be carried and used at any time. The system is built using Sketchware, PHP, MariaDB Database and API.